Investing in health preparedness, response and resilience: a genomics costing tool focused on next generation sequencing - Akande, Oluwatosin Wuraola; Afrough, Babak; Amante, Maria; Carter, Lisa; Cunningham, Jane; Hull, Noah Clayton; Inamdar, Leena; Jaguparov, Alexandr; Marklewitz, Marco; Musul, Biran; Norberg, Ashley; Pereyaslov, Dmitriy I.; et al. (Frontiers in Public Health, 2024)
The world has seen unprecedented gains in the global genomic surveillance capacities for pathogens with pandemic and epidemic potential within the last four years. To strengthen and sustain the gains made, WHO is working with countries and partners to implement the Global Genomic Surveillance Strategy for Pathogens with Pandemic and Epidemic Potential 2022-2032. A key technical product developed through these multi-agency collaborative efforts is a genomics costing tool (GCT), as sought by many countries. This tool was developed by five institutions -Association of Public Health Laboratories, FIND, The Global Fund to Fight AIDS, Tuberculosis and Malaria, UK Health Security Agency, and the World Health Organization. These institutions developed the GCT to support financial planning and budgeting for SARS-CoV-2 next-generation sequencing activities, including bioinformatic analysis. The tool costs infrastructure, consumables and reagents, human resources, facility and quality management. It is being used by countries to 1) obtain costs of routine sequencing and bioinformatics activities, 2) optimize available resources, and 3) build an investment case for the scale-up or establishment of sequencing and bioinformatics activities. The tool has been validated and is available in English and Russian at https://www.who.int/publications/i/item/9789240090866 . This paper aims to highlight the rationale for developing the tool, describe the process of the collaborative effort in developing the tool, and describe the utility of the tool to countries. overarching objective to support international efforts to strengthen genomic data sharing for pathogens of public health concern.